Tinjauan Strategi Pemasaran PT. Yumna Berkah Nusantara Tasikmalaya - Asep Saepul Milah; Ernawati (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
The Muslim fashion business in the Tasikmalaya region continues to grow; given that the majority of the population is Muslim, Muslim fashion is not merely a matter of preference but a necessity. As the number of Muslim fashion businesses increases, competition has intensified. PT. Yumna Berkah Nusantara Tasikmalaya operates in the Muslim fashion sector by implementing a marketing mix strategy that encompasses the variables of product, price, promotion, and place (distribution). This study examines the implementation of this marketing mix strategy, identifies obstacles, and seeks relevant solutions. The study employs a descriptive qualitative method, utilizing primary and secondary data collected through observation, interviews, documentation, and triangulation. A saturated sampling technique was used, and data analysis was conducted using an interactive model comprising data reduction, data presentation, and conclusion drawing. The results indicate that PT. Yumna Berkah Nusantara Tasikmalaya has implemented a marketing mix strategy. However, the company faces obstacles such as limited human resources, shortcomings in production planning, suboptimal product innovation, business competition, and less-than-competitive pricing. Proposed solutions include investing in resources, conducting market research, developing product innovations, identifying competitive advantages, and segmenting the customer base.